Focus on physics competitions—a résumé concerning submissions in 2020 and an encouragement for future submissions - Fösel, Angela (European Journal of Physics, 2021)
The journal collection 'Focus on Physics Competitions' of the European Journal of Physics (EJP) is an ongoing collection within the European Journal Physics (EJP). In the year 2020, five articles have been submitted within this series. This editorial will briefly sum up the content and ideas of those articles. In addition, the concept of this collection is explained in order to ensure the objectives of this collection are clear and evident for future submissions.<br
Keywords: physics competitions